Contribution of rice straw to potassium supply in rice-fallow-rice cropping pattern (Bangladesh Journal of Agricultural Research, 2010)
A field experiment was conducted through 2001-2004 at the Bangladesh Rice Research Institute (BRRI), Gazipur Farm with a view to determining the contribution of rice straw to K supply and K-use efficiency for the next crop in Rice-Fallow-Rice cropping pattern. Two levels of chemical potassium-0 (K0) and 66 kg K/ha (K66) from muriate of potash (MoP)- were tested with or without straw incorporation. Results showed that the use of K either from inorganic fertilizer or from rice straw increased the plant height, panicles/m2, grain and straw yields of rice in both Boro and T. Aman seasons. However, the effect of K was more distinct in Boro season. On an average, 1.33 t/ha yield benefit of Boro rice was obtained with rice straw incorporation in K0 plot. Application of K significantly increased the total K and P uptake of rice crops. Agronomic efficiency, partial factor productivity and physiological efficiency of K decreased with the increasing K level regardless of K sources in Boro season. Potassium replenishment through chemical fertilizer was not sufficient to balance K. However, incorporation of rice straw showed a positive K balance. Positive perceptible changes in soil characteristics and soil nutrient status (N, P and K) were observed due to K fertilization either from inorganic (MoP) or from organic sources. Key Words: Contribution of rice straw application; K-supply; rice-fallow-rice cropping pattern. DOI: 10.3329/bjar.v34i4.5839Bangladesh J. Agril. Res. 34(4) : 633-643, December 2009